2009
DOI: 10.1016/j.neulet.2009.02.028
|View full text |Cite
|
Sign up to set email alerts
|

Loss of alpha power is related to increased gamma synchronization—A marker of reduced inhibition in tinnitus?

Abstract: Tinnitus is the perception of sound in the absence of any external auditory stimulus. Based on previous research we have proposed a framework which postulates that the reduction of ongoing inhibitory alpha activity in tinnitus subjects favors a synchronization of neurons in the gamma frequency range while in a resting state. In the present work we are validating the existence of an inverse relationship between auditory gamma and alpha activity in tinnitus and control subjects using Magnetoencephalography. Tinn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
52
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 34 publications
8
52
1
Order By: Relevance
“…This finding corroborates with previous studies that indicate that the amount of gamma band activity is correlated to the subjectively perceived tinnitus loudness (van der Loo et al, 2009;Vanneste et al, 2012) and a decrease in alpha power is associated with an increase in gamma power in tinnitus (Adamchic et al, 2012;Adamchic et al, 2014;Lorenz et al, 2009;Ramirez et al, 2009). To a certain extent this fits with the concept of thalamocortical dysrhythmia (Llinas et al, 2005;Llinas et al, 1999).…”
Section: Discussionsupporting
confidence: 92%
“…This finding corroborates with previous studies that indicate that the amount of gamma band activity is correlated to the subjectively perceived tinnitus loudness (van der Loo et al, 2009;Vanneste et al, 2012) and a decrease in alpha power is associated with an increase in gamma power in tinnitus (Adamchic et al, 2012;Adamchic et al, 2014;Lorenz et al, 2009;Ramirez et al, 2009). To a certain extent this fits with the concept of thalamocortical dysrhythmia (Llinas et al, 2005;Llinas et al, 1999).…”
Section: Discussionsupporting
confidence: 92%
“…It has been shown that episodes with enhanced alpha activity in sensory areas are characterized by reduced excitability in the respective sensory modality, while episodes with low alpha activity (i.e., alpha desynchronization) are associated with enhanced neuronal excitability of this area [20, 21, 36, 37]. In this context, electro- und magnetoencephalographic recordings of auditory activity over sensory areas can be interpreted as a measurement of a neuronal mechanism gating sensory information processing.…”
Section: Discussionmentioning
confidence: 99%
“…Both positron emission tomography (PET) and functional Magnetic Resonance Imaging (fMRI) (Adjamian et al 2009;Lanting et al 2009) have demonstrated changes of neuronal activity in central auditory pathways in tinnitus patients. Electroencephalograhy (EEG) and magnetoencephalography (MEG) data have shown a reduction of alpha power and an increase in slow waves and in gamma activity in auditory areas (Weisz et al 2007a,b;van der Loo et al 2009;Lorenz et al 2009), a pattern which has been proposed to emerge after thalamic deafferentiation from auditory input (Llinas et al 1999(Llinas et al , 2005. This increased synchronized fi ring in the gamma band together with decreased lateral inhibition after deafferentation may induce cortical reorganization via simple Hebbian mechanisms (Eggermont and Roberts 2004) and neural plasticity which fi nally results in alterations of the tonotopic map (Muhlnickel et al 1998).…”
Section: Neurobiology Of Tinnitus and Depressionmentioning
confidence: 99%